Oculomotor Nerve Teratoma - Moore, Kevin R. (AJNR Am J Neuroradiol, 2001)
Summary: The case of a rare, mature teratoma of the oculomotor nerve manifesting as an interpeduncular cistern mass is presented. A basilar tip aneurysm initially was suspected on the basis of lesion location and MR imaging appearance. Subsequent CT and catheter angiography studies were atypical for aneurysm, leading to surgical biopsy. Pathologic analysis revealed a well-circumscribed mass composed of mature representatives of all three major cell lines characteristic of mature teratoma. The imaging findings are described, and a brief literature review is provided.